The Wizard of Oz [videorecording (DVD)] - Fleming, Victor, 1889-1949; Garland, Judy; Morgan, Frank, 1890-1949; Lahr, Bert, 1895-1967; Bolger, Ray; Baum, L. Frank (Lyman Frank), 1856-1919 (Warner Bros. family entertainment., 1999)
Musical fantasy tale about a little Kansas girl named Dorothy who visits the magical land of Oz.